Molecular Identification of Newly Recorded Louse Columbicola tschulyschman Eichler (Phthiraptera: Philopteridae) From Saudi Arabia With a Note on Genus Columbicola spp. Phylogeny. Issue 6 (24th September 2022) - Alotaibi, Noura J; Al-Turaiki, Isra M; Alajmi, Reem; Fouzi, Boulkenafet; Amjad Bashir, Muhammad; Almusawi, Zainab; Metwally, Dina M; Alzarzor Alajami, Mais A; Alajmi, Fatemah E; Nasser, Mohamed G
Abstract: Chewing lice comprise a large group of ectoparasites that colonize and adversely affect several domestic and wild birds including pigeons. In Saudi Arabia, there is a lack of studies describing such ectoparasites and their infestation rates. Through this work, a new record, Columbicola, tschulyschman Eichler ( C. tschulyschman Eichler ) was collected from domestic pigeons (Columba livia domestica, Linnaeus). The collected C. tschulyschman Eichler was morphologically identified based on specific taxonomic keys. Mitochondrial ( COI ) and nuclear ( EF-1α ) gene fragments were used for molecular identification and phylogenetic reconstruction. In this study, the C. tschulyschman Eichler accounted for around 69.40%. To our knowledge, this is the first report of C. tschulyschman Eichler in Riyadh, Saudi Arabia. To improve the tree topology and differentiate between genera, further studies should utilize the 16s rRNA.